2020
DOI: 10.1111/are.14582
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulphide in Pacific white shrimpPenaeus vannameiunder varying oxygen and pH levels

Abstract: Sulphide is one of the known environmental stressors, which potentially binds to cytochrome C oxidase (COX), a key enzyme in the electron transport chain, thereby blocking oxygen transport and ATP production. To ascertain the toxic effects of sulphide on Pacific white shrimp, Penaeus vannamei, two distinct exposure experiments were carried out with varying concentration of sulphide (0–1 mg/L), dissolved oxygen (normoxia and hypoxia) and pH values (8.2, 6 and 5). The activity of enzymes viz COX, superoxide dism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 52 publications
0
5
0
1
Order By: Relevance
“…In the current study, mitochondrial cytochrome c oxidase (mtCOX), mitochondrial manganese superoxide dismutase (mtMnSOD), and glutathione S -transferase θ1 (GST-θ1) in FC/LC and DC/FC comparisons were collectively downregulated. Thulasi et al reported that COX and mitochondrial-like proteins could be associated with mitochondrial membrane damage due to the high levels of ROS production under severe oxidative stress induced by food deprivation. , The mtMnSODs, key antioxidant enzymes that contain manganese, can catalyze anion disproportionation and have been reported to be involved in the innate immune response of crabs. , They are considered the first line of defense against oxidative stress induced by excessive ROS beyond the threshold limits resulting from respiratory bursts . A GST catalyzes the conjugation of glutathione (GSH) with toxic reactive metabolites and is considered a detoxification enzyme against the chemotoxicity of xenobiotics .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, mitochondrial cytochrome c oxidase (mtCOX), mitochondrial manganese superoxide dismutase (mtMnSOD), and glutathione S -transferase θ1 (GST-θ1) in FC/LC and DC/FC comparisons were collectively downregulated. Thulasi et al reported that COX and mitochondrial-like proteins could be associated with mitochondrial membrane damage due to the high levels of ROS production under severe oxidative stress induced by food deprivation. , The mtMnSODs, key antioxidant enzymes that contain manganese, can catalyze anion disproportionation and have been reported to be involved in the innate immune response of crabs. , They are considered the first line of defense against oxidative stress induced by excessive ROS beyond the threshold limits resulting from respiratory bursts . A GST catalyzes the conjugation of glutathione (GSH) with toxic reactive metabolites and is considered a detoxification enzyme against the chemotoxicity of xenobiotics .…”
Section: Resultsmentioning
confidence: 99%
“…Thulasi et al reported that COX and mitochondrial-like proteins could be associated with mitochondrial membrane damage due to the high levels of ROS production under severe oxidative stress induced by food deprivation. 32,33 The mtMnSODs, key antioxidant enzymes that contain manganese, can catalyze anion disproportionation and have been reported to be involved in the innate immune response of crabs. 34,35 They are considered the first line of defense against oxidative stress induced by excessive ROS beyond the threshold limits resulting from respiratory bursts.…”
Section: Validation Of Tmt-based Proteomics Approachesmentioning
confidence: 99%
“…These results in low DO condition. Another problem that may arise from this situation is the possibility of increasing impurities in the water [4]. Those findings demonstrated that low DO is an enormous threat for the biotic components in the marine ecosystems.…”
Section: Literature Review and Problem Statementmentioning
confidence: 96%
“…The H2S formed creates a bad odour and black colour in the sediment, and is also toxic to the shrimp that dwell at the pond bottom. Sulphide toxicity to shrimp depends on both the H2S concentration and pH (Vismann, 1996;Thulasi et al, 2020), with lethal concentrations to kill 50% of the population (LC50) values ranging between 0.0087 and 0.033 mg/L H2S, depending on shrimp species and growth phase of the shrimp (H.-C. Chen, 1985;US-EPA, 2011). Exposure to sub-lethal concentrations of H2S lowers shrimp resistance to diseases and causes tissue corrosion (Suo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%